Mapping of a Cellulose-Deficient Mutant Named dwarf1-1 in Sorghum bicolor to the Green Revolution Gene gibberellin20-oxidase Reveals a Positive Regulatory Association between Gibberellin and Cellulose Biosynthesis . Issue 1 (21st July 2015) - Petti, Carloalberto; Hirano, Ko; Stork, Jozsef; DeBolt, Seth
Abstract : A gibberellin oxidase exposes the regulatory association between gibberellic acid and cellulose biosynthesis during cell expansion. Abstract: Here, we show a mechanism for expansion regulation through mutations in the green revolution gene gibberellin20 ( GA20 ) -oxidase and show that GAs control biosynthesis of the plants main structural polymer cellulose. Within a 12, 000 mutagenized Sorghum bicolor plant population, we identified a single cellulose-deficient and male gametophyte-dysfunctional mutant named dwarf1-1 ( dwf1-1 ). Through the Sorghum propinquum male/ dwf1-1 female F2 population, we mapped dwf1-1 to a frameshift in GA20-oxidase . Assessment of GAs in dwf1-1 revealed ablation of GA. GA ablation was antagonistic to the expression of three specific cellulose synthase genes resulting in cellulose deficiency and growth dwarfism, which were complemented by exogenous bioactive gibberellic acid application. Using quantitative polymerase chain reaction, we found that GA was positively regulating the expression of a subset of specific cellulose synthase genes. To cross reference data from our mapped Sorghum sp. allele with another monocotyledonous plant, a series of rice ( Oryza sativa ) mutants involved in GA biosynthesis and signaling were isolated, and these too displayed cellulose deficit. Taken together, data support a model whereby suppressed expansion in green revolution GA genes involves regulation of cellulose biosynthesis.